The management and outcomes of Staphylococcus aureus bacteraemia at a South African referral hospital: A prospective observational study. (August 2018) - Steinhaus, Nicola; Al-talib, Mohammed; Ive, Prudence; Boyles, Tom; Bamford, Colleen; Davies, Mary-Ann; Mendelson, Marc; Wasserman, Sean
Abstract: Objectives: Data on the management and outcomes of Staphylococcus aureus bacteraemia (SAB) in resource-limited settings are limited. The aim of this study was to describe a cohort of South African patients with SAB, and explore the factors associated with complicated infection and death. Methods: This was a prospective observational study of patients over the age of 13 years admitted to a South African referral hospital with SAB. Results: One hundred SAB infection episodes occurring in 98 patients were included. SAB was healthcare-associated in 68.4%; 24.0% of all cases were caused by methicillin-resistant S. aureus (MRSA). Ninety-day mortality was 47.0%, with 83.3% of deaths attributable to SAB. There was a trend towards increased 90-day mortality with MRSA infection (odds ratio (OR) 1.28, 95% confidence interval (CI) 1.0–15.1) and the presence of comorbidities (OR 4.1, 95% CI 1.0–21.6). The risk of complicated infection was higher with non-optimal definitive antibiotic therapy (OR 8.5, 95% CI 1.8–52.4), female sex (OR 3.8, 95% CI 1.1–16.3), and community-acquired infection (OR 7.4, 95% CI 2.0–33.1). Definitive antibiotic therapy was non-optimal in 22.6% of all cases. Conclusions: SAB-related mortality was high. A large proportion of cases may be preventable, and there is a need for improved antibiotic management.